Reproductive disorders linked to the interaction between sex steroid and thyroid hormonal activities, oxidative stress responses, and the rate of metabolism of tris (1,3-dichloro-2-propyl) phosphate (TDCPP) in zebrafish - Cho, Sung-Hee; Pyo, Heesoo; Lee, Jangjae; Zee, Seonggeun; Kim, Eunyoung; Park, June-Woo; Park, Chang-Beom (Academic Press, 2023)
The objective of this study was to assess the thyroid hormone disruption and reproductive dysfunction effects of the bioaccumulation and rate of mechanism in zebrafish exposed to tris(1,3-dichloro-2-propyl) phosphate (TDCPP), with stress responsiveness. The fish were exposed to test concentrations of TDCPP (0, 0.06, 0.3, 1.5 mu g/mL) for 21 days, in accordance with no observed adverse effect level (i.e., < EC10) for zebrafish embryos. The bioaccumulation of TDCPP was found to be significantly higher in female zebrafish, while the metabolic rate was significantly higher in male zebrafish at all concentrations studied. The thyroid hormone (triiodothyronine [T3] and thyroxine [T4]) levels and sex steroid (i.e., estrogen, androgen, and progesterone) levels were significantly increased only in female zebrafish exposed to TDCPP, and no significant difference was observed in male zebrafish, although their cortisol levels increased. The response to TDCPP can, therefore, be considered sex-specific. The results of this study demonstrate for the first time, that the different response in the bioaccumulation and metabolic rate of TDCPP in males and females. The results also indicate that TDCPP alters thyroid hormone levels, furthermore, as steroidogenesis is related to reproductive function with differing response in males and females. TDCPP can be assumed to exert reproductive toxicity via disruption of thyroid and steroid synthesis through a slow metabolic rate in the whole body after exposure. Consequently, our proposed methodological approach to assess the interactions of thyroid and steroid biosynthesis and metabolic rate of TDCPP with reproductive toxicity will serve a testing strategy to examine the adverse outcomes of emerging environmental chemicals.